SOCIAL DISTANCING: ALIENASI GAYA BARU (?) - Yoga Febriano (Aggiornamento, 2020)
This article puts attention on human’s relation with other in pandemic of covid-19 times. There is a problem about using social distancing and physical distancing phrases. Its both is not only making any debates, especially for intellectual, however, influenced how human seeking the meaning about his relation with others. In the article is given some of themes who arranged systematically to description the problem which is. Some of themes e.i. etymology of social and physical distancing; the meaning of human’s relation in pandemic times; and the last one description who would like tell that human has living under social alienation which is caused by social distancing phrase. This article has used literature methodology. It was using some of texts who relevant and describable about the human’s relation especially in pandemic times. From its texts are found some of idea who constructs and be the main idea in the article. Finally all about that is finished with a conclusion that social distancing phrase has alienated individual from human’s society. The truly phrase is physical distancing